Co-simulation of longitudinal slip control systems for an electric vehicle in CarSim and Matlab (2017)
This project addresses the problem of longitudinal traction and anti-lock brake control of an all-wheel drive In-wheel motor electric vehicle (IWMEV) in the presence of different kinds of road conditions such as snow or wet asphalt. The objective of the traction controller is to maximize the tractive force that moves the vehicle forward while accelerating, and the anti-lock brake controller attempts to minimize the distance required to stop the vehicle while braking. For the traction problem, a PID and a sliding mode controller are proposed and tested. For the braking problem, a PID with an adaptive Extremum Seeking scheme is proposed and tested. The vehicle and road environment are modeled in co-simulation with CarSim and MATLAB/Simulink.